Multilingualism in the Canadian Educational Context: Identity, Belonging, and Translanguaging Pedagogies - Ahmad Zirak Ghazani (Journal of Research in Social Sciences and Language)
In this study, I examine the nature of multilingual education, which provides cultural, social, and economic affordances yet poses considerable emotional and academic challenges for learners. I explore how dominant languages impact multilingual learners’ identity and sense of belonging and identity negotiation, particularly within the Canadian educational context. Through a multiple case study involving four Iranian-Canadian minors and their parents, I use multimodal data collection methods, including semi-structured interviews with children and their parents, children’s writings, and multisemiotic representations, to capture the complexities of learners’ communicative repertoires. Participants’ narratives revealed tensions between their multilingual identities and the monolingual ideologies entrenched in educational systems. However, the study reveals that translanguaging pedagogy, which has emerged as a crucial pedagogical strategy, can enable learners to draw on their unitary communication competence without suppressing part of their linguistic repertoire to enhance understanding and reduce cognitive pressures. This research signals the imperative to operationalise translanguaging as a classroom practice. Dialogic tasks and teacher mediation that affirm multilingual expression can be embedded into everyday instructions. These findings illuminate the imperative for educational reform policies that go beyond classroom practices to address the broader monolingual and neoliberal ideologies, which prioritise the dominant state languages as pathways to prosperity. I argue that such reforms must not be tokenistic and must meaningfully engage with the sociocognitive and cultural challenges multilingual learners face to ensure that their diverse linguistic needs are fully supported.